Framing â€œTong Ngin Fan Ngin Jit Jongâ€ Slogan as Construction of Three Online Media Framing at Bangka - Sya, Meta; Marta, Rustono Farady (Faculty of Communications Science, Dr. Soetomo University, 2019)
This research discusses about frame of online newspaper that convey the slogan of Tong Ngin Fan Ngin Jit Jong. The slogan itself reflects the equality slogan for both Malay and Chinese ethnics in Bangka Belitung Islands Province. The deliverance of this issue departs from the framing differences of the